Cyber-victimization—influence of parental rules and impact on mental health among Indian adolescents - Tamarana, Rameshbabu; Mathur, Mansi; Madhusudan, Varsha; Annapurna Kiranmai, P. (Frontiers in Psychology, 2025)
IntroductionIn the contemporary digital age, cyberspace offers numerous benefits but also presents significant risks, including cyber-victimization. Adolescents, as frequent internet users, are particularly vulnerable to such experiences. This study examines the relationship between parental regulations on internet usage and the incidence of cyber-victimization among Indian adolescents, while also assessing the impact of cyber-victimization on mental health outcomes such as stress, anxiety, and depression.MethodsA sample of 224 adolescents (Mean age = 16.5 years SD = 2.34) was surveyed using standardized measures of cyber-victimization and mental health.ResultsMultiple linear regression analyses revealed that written-verbal cyber-victimization was a significant predictor of stress (β = 0.18, p < 0.05), while impersonation, written-verbal cyber-victimization, and online exclusion significantly predicted anxiety (p < 0.05). However, none of the cyber-victimization subtypes significantly predicted depression, and the overall model accounted for only 4% of its variance.DiscussionThese findings suggest that while cyber-victimization is linked to stress and anxiety, its influence on depression may be more complex. Furthermore, the Pearson correlation analysis indicated a negligible association between cyber-victimization and parental rules on internet usage (r = 0.039), suggesting that parental regulations alone may not effectively mitigate cyber-victimization risks. Given these findings, interventions focusing on resilience-building, digital literacy, and peer support may be more effective in protecting adolescents from the adverse effects of cyber-victimization. Future research should explore alternative protective factors and preventive strategies to promote adolescent well-being in digital spaces.